2021
DOI: 10.1101/2021.03.06.21253051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 1 to 1000 SARS-CoV-2 reinfection proportion in members of a large healthcare provider in Israel: a preliminary report

Abstract: With more than 100 million confirmed COVID-19 cases as of March 2021, reinfection is still considered to be rare. In light of increasing reports of reinfected COVID-19 patients, the need to better understand the real risk for reinfection is critical, with potential effects on public health policies aimed at containing the spread of SARS-CoV-2. In this descriptive preliminary report, we conducted a large-scale assessment on the country level of the possible occurrence of COVID-19 reinfection within the members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 14 publications
(15 reference statements)
4
58
0
Order By: Relevance
“…Overall, we observed that (i) if the time lag between discharge and RP of SRAS-CoV-2 is at most 28 days, these might be reinfection or relapse of previous infection; (ii) if the time lag is 2 months, it is more likely to be reinfection; and (iii) if the time lag is 3 months or above, it is very likely to be true reinfection (17). However, the most reliable way is to perform sequencing twice and get two different strains of the virus.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Overall, we observed that (i) if the time lag between discharge and RP of SRAS-CoV-2 is at most 28 days, these might be reinfection or relapse of previous infection; (ii) if the time lag is 2 months, it is more likely to be reinfection; and (iii) if the time lag is 3 months or above, it is very likely to be true reinfection (17). However, the most reliable way is to perform sequencing twice and get two different strains of the virus.…”
Section: Discussionmentioning
confidence: 77%
“…However, this issue needs urgent attention to investigate whether RP-SARS-CoV-2 patients could be a serious public health problem. However, some studies reported that a small proportion (about 1%) of the population can be RP for SARS-CoV-2, and possibly due to reactivation or reinfection (16,17). Furthermore, previous reports (7,34,35) highlighted that RP-SARS-CoV-2 is less likely to cause serious problems to public health since the rate of RP seems low (about 1%), and new infections declining after recovery from the first episode of the infection (16,35), which is likely due to the suspected herd immunity (97,98).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24.21262415 doi: medRxiv preprint apart. 12 Using similar criteria, population-based studies demonstrated natural immunity 13,14 with no signs of waning immunity for at least 7 months, though protection was lower for those aged 65 or older 9 .…”
Section: Introductionmentioning
confidence: 98%
“…The course of COVID-19 in these people was mildly symptomatic and no one required hospitalization. SARS-CoV-2 infections after vaccination have been reported sporadically [37,38], but they raise important issues regarding the duration of immunity after natural infection and the extent of protection after vaccination, as well as the transmission of the virus. We conducted regular immunological surveillance for 8 seronegative participants and observed that 4 months after the rst vaccinations, anti-SARS-CoV-2 IgG levels were lower and continued to decline.…”
Section: Discussionmentioning
confidence: 99%